(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2021)
This study aims to identify the characteristics of human resources in slaughterhouses category I and category II, as well as to analyze the performance and efficiency of human resources in slaughterhouses category I and category II. Location samples and respondents were determined purposively. The variables observed were the characteristics of my human source, my human source performance, and the efficiency of my human source performance in category I and category II slaughterhouses. The results showed that the characteristics of category I and category II employees had an average high school education, 30-40 years of age and 10-20 years of work. The performance of my human resources (work results, skills, discipline and responsibility) of each slaughterhouse has a fairly good percentage, slaughterhouse for category I (77.66-80.95%) and slaughterhouse for category II (81.68-83.59%) . The performance efficiency figures for the employees of the slaughterhouse category I and category II are similarly close to number 1 indicating that the employees’ working time is used efficiently.